Peran Kiai Langgar dalam Merawat Ajaran Islam Wasatiyah di Madura - AR, Samsul; Supriyadi, Moh. (Proceedings of Annual Conference for Muslim Scholars, 2022)
The Indonesian plurality needs to be preserved and maintained in order to continue the unity of Indonesia. One of the Islamic teachings that taught plurality is the understanding of islam wasatiyah. This understanding needs to be taught to the generations of nations so that the generations of nations become the generations that can be spread out of Islamic teachings. One of the most important things to teach islam wasatiyah is a kiyai langgar. The presence of kiai langgar (priest) in the middle of the rural community is very necessary because the kiai become an example and role model for the societies. Kiai langgar becomes a magnet for society because his word becomes an argument for the element of society. Even, from long time ago up to this time, kiai langgar is being an educational subject, a local wisdom consevionest, and an Indonesian consevionest unity values. Although His existence has not recognized by everyone, but he has been consistently continued contributing to the Indonesian people. And also his existence became an oasis in the lives of the Indonesian people. The presence of a kiai Langgar becomes a blessing for the villager. the presence of kiai langgar becomes a solver of society's problems in daily life. He becomes a place where people can complain of grief and all the problems of conditionality, and become an avenger if there is a dispute between society and others. This main role becomes kiai langgar is an important man to teach Islamic religion from the village. This research studies the role of kiai langgar in treating Islamic wasatiyah teachings on Madura Island. This study uses qualitative methods with discrete analysis approaches.